HINDU TEMPLE ART AND ARCHITECTURE OF SOME SHAIVA TEMPLES OF THE COASTAL BELT OF ODISHA IN EASTERN INDIA - Mohapatra, Ratnakar; Majhi, Hutasan (International Journal of Psychosocial Rehabilitation, 2020)
The artistic technique and architectural features of the extant Shaiva temples of the coastal-belt of Odisha are the important aspects of the Hindu temple art of Odisha in Eastern India. The extant temples of the coastal areas of the undivided Cuttack and Puri districts possess the features of Kalinga style of temple architecture of Odisha. Really, some Shaiva temples of the coastal-belt of Odisha are very important considering their religious significance and artistic techniques. The earlier art historians and senior scholars had not dealt with detail in all the Shaiva temples of the coastal-belt of Odisha, for which, five temples are taken here for the subject of our discussion. These five Shaiva temples are such as 1.Vandeshvara Temple at Chahata, 2. Grameshvara temple at Mahanga, 3. Gatishvara Temple at Sundargrama , 4. Nrutyeshvara temple at Nasikesvara, and 5. Sankaresvara Temple of Narua-Sankaresvara. The aim of this article is to focus on artistic techniques and architectural features alongwith the religious significance of the above Shaiva temples of the coastal-belt of Odisha in Eastern India. Methodologically, both the primary and secondary sources have been used for the writing of this article.